Continuous Positive Airway Pressure and the Burden of Care for Transient Tachypnea of the Neonate: Retrospective Cohort Study - Gizzi, Camilla; Klifa, Roman; Pattumelli, Maria Grazia; Massenzi, Luca; Taveira, Melanie; Shankar-Aguilera, Shivani; De Luca, Daniele (American Journal of Perinatology, 2015)
Objectives Transient tachypnea of the neonate (TTN) is the commonest neonatal respiratory disorder. Given TTN physiopathology, continuous positive airway pressure (CPAP) could be indicated for its treatment, but no data are available. Our aim is to clarify if CPAP might reduce the TTN burden of care.Design Retrospective multicenter cohort study enrolling 42 full-term TTN babies treated with CPAP and 40 with oxygen supplementation.Results CPAP-treated infants show shorter intensive care unit stay (CPAP, 2.5 ± 2 vs. Oxygen, 4.4 ± 2.6 days; adjβ, −2.1 [95% confidence interval (CI): −3.1; −1]); p < 0.001) and lower maximal oxygen fraction (adjβ, −4.7 [95% CI: −7.7; −1.7]; p = 0.003). Air leak incidence was similar between the groups (adjOR, 0.36 [95% CI: 0.1; 1.1); p = 0.08). Patients' comfort as per EDIN score was also unchanged. Given the shorter length of intensive care, the use of CPAP for treating TTN would spare on average around 7,000 Euros/infant.Conclusion CPAP seems a useful therapeutics for TTN, as it may reduce the burden of care without increasing air leaks or patients' discomfort.
Keywords: transient tachypnea; neonate; continuous positive airway pressure; NICU stay; burden of care